Sauvegarde et valorisation du fonds d’archives familiales de Jean-Joseph Rabearivelo à Madagascar - Laurence Ink (Continents manuscrits)
Significant but still not recognisable enough figure of Malagasy and international literature, Jean-Joseph Rabearivelo (1903-1937), was : poet, journalist and critic, playwright and novelist, historian of his tradition at a time. He collected and translated old texts as well as of the modern ones. The adventure, which started at the end of 2008, finished with publishing Rabearivelo’s complete works (AUF/ITEM, CNRS Éditions, Collection Planète Libre, Paris, two tomes, 2010 and 2012), consisted in maintaining the considerable family archives (over 800 manuscripts, typescripts, published texts and working papers) entrusted by the Rabearivelo’s assignees to the Institut Français of Madagascar (Antananarivo). The archives have been sorted, scanned and put in neutral packaging in situ. Finally, Rabearivelo’s writings, the vast majority of whom has never been issued, have been published in a genetic approach. This innovative experience, based on a methodology requiring a continuous adaptation to demands of geography, research and of publishers, should be considered as a typical example for better approach of literary archives, threatened in a vast number of Southern Francophone countries.